2010
DOI: 10.1364/boe.1.000367
|View full text |Cite
|
Sign up to set email alerts
|

Depth-resolved imaging and detection of micro-retroreflectors within biological tissue using Optical Coherence Tomography

Abstract: A new approach to in vivo biosensor design is introduced, based on the use of an implantable micron-sized retroreflector-based platform and non-invasive imaging of its surface reflectivity by Optical Coherence Tomography (OCT). The possibility of using OCT for the depth-resolved imaging and detection of micro-retroreflectors in highly turbid media, including tissue, is demonstrated. The maximum imaging depth for the detection of the micro-retroreflector-based platform within the surrounding media was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In the absence of absorption, the most important factors in determining this degradation are the imaging depth in the tissue, z 0 , the scattering coefficient, μ s , and scattering anisotropy, g 6 8 9 . Thus far, studies of their effects on OCT image quality have been confined to the use of Gaussian beams and, although several of these have analysed the effect of scattering anisotropy 10 11 , most have studied the impact of only the scattering coefficient 4 5 12 13 at various depths.…”
mentioning
confidence: 99%
“…In the absence of absorption, the most important factors in determining this degradation are the imaging depth in the tissue, z 0 , the scattering coefficient, μ s , and scattering anisotropy, g 6 8 9 . Thus far, studies of their effects on OCT image quality have been confined to the use of Gaussian beams and, although several of these have analysed the effect of scattering anisotropy 10 11 , most have studied the impact of only the scattering coefficient 4 5 12 13 at various depths.…”
mentioning
confidence: 99%
“…In OCT, this can be quantified easily by measuring the optical attenuation [2,4,6,7,9,10,20,21,[27][28][29][30][31][32][33]. However, in this study, the constant change of the fluid volume during the clearing process resulted in dynamic defocusing of the OCT signal and, thus, affecting the values of the OCT signal slope.…”
Section: Resultsmentioning
confidence: 84%
“…Regarding this problem, a micro-retroreflector-based gold platform with a fixed distribution pattern has been designed and manufactured to provide highly-reflected light and also the possibility of implantation [33]. For the imaging with OCT, the platform has been demonstrated to be able to offer well-specified region and good signal-to-noise ratio [35]. …”
Section: Resultsmentioning
confidence: 99%
“…More recently, we have demonstrated that OCT has the capability of depth-resolved imaging of highly-reflective micro-structures under tissue up to 910 μ m in depth [35], and, thus, OCT could be used to detect the change of the reflection of light from a gold mirror surface under tissue and to monitor the microparticle number based on the scattering properties of these particles. Since we expect that the glucose concentration can be well represented by the amount of bound microparticles, the sensitivity and specificity of the proposed sensing system are highly dependent on how well the microparticles can be resolved by OCT and how well the signal from OCT and the microparticle density are correlated.…”
Section: Introductionmentioning
confidence: 99%